The Effect of Refugee Inflows on Host Communities - Alix-Garcia, Jennifer; Saah, David (World Bank, 2012)
Despite the large and growing number of humanitarian emergencies, there is little economic research on the impact of refugees and internally displaced people on the communities that receive them. This analysis of the impact of the refugee inflows from Burundi and Rwanda in 1993 and 1994 on host populations in western Tanzania shows large increases in the prices of nonaid food items and more modest price effects for aid-related food items. Food aid is shown to mitigate these effects, though its impact is smaller than that of the increases in the refugee population. Examination of household assets suggests positive wealth effects of refugee camps on nearby rural households and negative wealth effects on households in urban areas.